Al-Hulul: Konsep Kontroversial dalam Ilmu Tasawuf - Nugraha, Ali Wahab; Nurrochman, Raihan; Ajmain, Maftuh (Lembaga Yasin AlSys, 2025)
This research is about how the science of Sufism has become a scientific field in which there are many controversies and polemics, and it has created terekat-tarekat in Islamic history to date. Throughout the history of Sufism, almost all Islamic scholars and intellectuals agree that it has existed since the Prophet Muhammad SAW. Where most Muslims recognize it as a scientific field of heart cleansing or a means to bring humans closer to God the Creator. Sufism has changed from era to era. In the past, from being limited to morals only and until now involving Aqidah, it raises many pros and cons. The concept of Al-Hulul is a teaching that states that God has chosen human bodies to reside in them with the nature of divinity after the human nature in the body is eliminated first. Several figures, most notably Al-Hallaj, pioneered the concept of Al-Hulul. The most famous Indonesian figure is Sheikh Siti Jenar.